2018
DOI: 10.1016/j.pec.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Heuristics and biases in cardiovascular disease prevention: How can we improve communication about risk, benefits and harms?

Abstract: Doctors need access to multiple CVD risk formats to communicate effectively about CVD prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“… 13 Bonner et al in their ‘talk-aloud’ study found that CVD tools that accounted for a greater number of risk factors were seen as more credible. 14 Our study suggests that the number of risk factors might be less important than whether the risk factors used match those that patients perceive as important.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“… 13 Bonner et al in their ‘talk-aloud’ study found that CVD tools that accounted for a greater number of risk factors were seen as more credible. 14 Our study suggests that the number of risk factors might be less important than whether the risk factors used match those that patients perceive as important.…”
Section: Discussionmentioning
confidence: 73%
“…Bonner and colleagues conducted a qualitative analysis of data from 25 Australian participants who were encouraged to ‘talk aloud’ when using two CVD risk communication tools. 14 They concluded that participants needed a reference point (example risk probabilities being anchored to ‘high risk’ and ‘low risk labels) to make sense of the probabilities and additionally found that CVD risk estimates derived from a larger number risk factors were felt to be more credible.…”
Section: Introductionmentioning
confidence: 99%
“…Although substantial work has been done to test the impact of framing effects (the tendency that people have to draw different conclusions from the same risk information, depending on whether it is expressed in terms of gains or losses) on screening or precautionary behaviours, most biases influencing health behaviour change have not yet been targeted. This is an issue since the effect of risk communication interventions could be enhanced with the use of adapted formats or metrics that specifically target such biases . Existing risk communication interventions for people with T2DM have shown mixed results, with many participants barely understanding the explanations of health professionals about risks and having poor recall of risk information .…”
Section: Background and Objectivesmentioning
confidence: 99%
“…This is an issue since the effect of risk communication interventions could be enhanced with the use of adapted formats or metrics that specifically target such biases. 10 Existing risk communication interventions for people with T2DM have shown mixed results, with many participants barely understanding the explanations of health professionals about risks and having poor recall of risk information. 11 There is an urgent need to improve risk communication in this area, making people with T2DM prime candidates to receive an intervention informed by behavioural economics.…”
Section: Backg Round and Objec Tive Smentioning
confidence: 99%
“…Recent calculators have generally used a 10-year time frame, and this may be more effective for conveying risk and motivating lifestyle changes. 30 There is increasing interest in 'heart age' calculators, which have been promoted around the world including in Australia, New Zealand and the UK. 31 While there are claims that giving patients an 'older' heart age can motivate them to change their lifestyles, a review of biological age formats found no evidence that this is more effective than absolute risk formats.…”
Section: Communicationmentioning
confidence: 99%